2009
DOI: 10.1111/j.1754-4505.2009.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral findings and dental treatment in a child with West syndrome

Abstract: West syndrome (WS) is a rare, severe form of epilepsy that typically manifests early in infancy. It is considered a malignant condition that combines episodes of spasms that occur in clusters (infantile spasm), hypsarrhythmia on the electroencephalogram, and neuropsychomotor delay. Although WS has been widely investigated from a medical standpoint, few reports have focused on the oral findings in patients with this syndrome. This article reports the case history of a 7-year-old child diagnosed with WS. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…As in other studies, there was a predominance of males in our sample; however, this might have been due to the limited number of individuals assessed, which in turn may have been to the low prevalence of the syndrome of its subnotification and or unawareness of family members of what the disease is.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…As in other studies, there was a predominance of males in our sample; however, this might have been due to the limited number of individuals assessed, which in turn may have been to the low prevalence of the syndrome of its subnotification and or unawareness of family members of what the disease is.…”
Section: Discussionmentioning
confidence: 56%
“…There are reports that the use of phenobarbital and valproic acid can induce gingival hyperplasia . Despite being an extremely rare condition three factors can be important in the manifestation of gingival hyperplasia: the use of a variation of the drug, plaque‐induced inflammatory changes, and genetic factors .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Case reports on West syndrome documented by Regis [10], Neta [11] and Khatri et al [12] showed similar intra oral findings i.e. multiple white spot lesions on labial surfaces, generalized tooth wear, altered chronology of teeth and gingival inflammation.…”
Section: Discussionmentioning
confidence: 68%